Real exchange rates, valuation effects and growth in emerging markets - Michael Bleaney; Liliana Castilleja Vargas (The University of Nottingham, Centre for Research in Economic Development and International Trade (CREDIT), 2007)
We compare the relationship between net capital inflows, real exchange rate movements and growth for twenty emerging markets and thirteen developed countries over the period 1985-2004. In developed countries low real exchange rates are associated with faster growth, but in emerging markets depreciations depress growth, even outside crisis periods, and are closely correlated with declines or reversals in net capital inflows. To investigate valuation effects of currency movements, we construct debt-weighted real exchange rate indices for emerging markets. We find only limited evidence that the contractionary effects of real depreciations in emerging markets can be attributed to valuation effects.
Keywords: F30; F40; 330; Capital flows; real exchange rates; growth; emerging markets; Kaufkraftparität; Kapitalmobilität; Wirtschaftswachstum; Aufstrebende Märkte; Welt